World Bank Lending for Financial Inclusion : Lessons from Reviews of Select Projects - Kumar, Anjali; Narain, Sushma; Rubbani, Swizen (World Bank Group, Washington, DC, 2015)
The purpose of the paper is to present a more granular view of such projects through the in-depth focus on a limited number of case studies, with a view to understanding what factors in the design of such lending have helped achieve objectives of expanded access, and what forms of interventions may have been less successful. It examines the nature of Bank lending vehicles, the partnering borrower institutions, the country environments in which its loans were extended, as well as broader elements of good practice that make for loan success. It examines the beneficiaries targeted and results achieved. It aims to draws lessons that suggest what factors could lead to success or failure in Bank operations focused on financial access. The remainder of the paper is organized as follows: section two briefly describes the set of the Bank s projects selected for detailed review. Sections three to six contain the core findings of the review. Section 3 focuses on alternative forms of borrower institutions that have served as vehicles for Bank projects, particularly, public sector banks, apex bank structures that include the private sector, rural banks, nonbanks, non-governmental organizations (NGOs) and microfinance institutions, in terms of the degree to which the Bank has been able to successfully partner with such institutions to expand financial access. It also looks at alternative forms of Bank loan design, policy-based loans, investment loans and lines of credit, Learning and Innovation Loans (LILs), matching grants, technical assistance and combinations thereof, and reviews evidence on the role of loan structure (including partnerships with other donors/lenders) and project success. Section four considers the effect of the broader business environment, in terms of financial regulation. Section five reviews elements of good practice that have contributed to success in lending that could be applicable to loans with any objective, and examines their application in the present context. Section six tries to construct a bottom line, reviewing available evidence on outcomes and impact; especially in terms of the ultimate beneficiaries reached. Section seven, the final section, summarizes the main messages emerging from the review and concludes with observations about ways forward.